INFLUENCE MASSAGE BABY TO FREQUENCY SPITTING UP IN BABIES 1-3 MONTHS OLD AT GRIYA HEALTHY MIDWIFE MOTHER KEPANJEN - Dinne Anggarawati; Sulistiyah (Yayasan Nuraini Ibrahim Mandiri, 2026)
Spitting up is frequent conditions​ occurs in babies age 1–3 months consequence Not yet ripe system digestion , especially sphincter esophagus part below . Frequency high spit up can cause discomfort in babies as well as anxiety in parents . One of the intervention non-pharmacological which can done For help lower frequency spit up is massage baby . Research This aim For know effectiveness massage baby to decline frequency spit up in babies 1–3 months old at Griya Healthy Midwife Mother Kepanjen . Research This use method quantitative with quasi-experimental design through pretest-posttest control group design approach . Sample study totaling 30 babies aged 1–3 months who experience spit up and share become group interventions and groups control of 15 respondents each . The sampling technique sample using purposive sampling. Group intervention given massage baby twice a week for 30 days , while group control only get maintenance routine without massage baby . Data collection was carried out use sheet observation frequency spit up before and after intervention . Data analysis using the Mann Whitney U Test with level significance α = 0.05. Research results show that before given intervention all over baby on both group experience spit up category heavy . After being given massage baby , happened decline frequency spit up in groups intervention become category mild and moderate , while in the group control part big baby still is in the category weight . Analysis results statistics show there is significant difference​ between group interventions and groups control after treatment given (p-value <0.05). Can concluded that massage baby effective as intervention non-pharmacological in lower frequency spit up in babies age 1–3 months .